Analyzing the Interrelationship between Land Surface Temperature, Environmental Indices, and Land Cover in Savar, Bangladesh - Oishe, Faria Rahman; Habib, Md. Ashraful; Tuya, Jannatun Hussna; Sabnam-E-Subha; Rafi, Md. Rafsanur (The Jahangirnagar Review, 2025)
This study explores how Land Surface Temperature (LST) is related to different land cover types, highlighting how vegetation and water bodies help reduce urban heat in Savar, Bangladesh. Using satellite imagery from the United States Geological Survey (USGS), LST and environmental indices— Normalized Difference Vegetation Index (NDVI), Normalized Difference Water Index (NDWI), Normalized Difference Built-Up Index (NDBI), Normalized Difference Moisture Index (NDMI), Soil-Adjusted Vegetation Index (SAVI), and Modified Normalized Difference Water Index (MNDWI) were employed to analyze the spatial distribution of LST and land cover types. The outcome reveals that densely built-up and industrial areas exhibit the highest LST due to impervious surfaces, while vegetated zones and water bodies, characterized by high NDVI, NDWI, and MNDWI values, show significantly lower LST. Areas with high NDMI and SAVI values also demonstrate effective temperature regulation by vegetation and soil moisture. Conversely, regions with high NDBI values correspond to higher LST, indicating the heat-retaining nature of urbanized areas. These findings underscore the importance of green and blue infrastructure in reducing urban heat and enhancing climate resilience. This study provides valuable insights for urban planners and policymakers, recommending the strategic expansion of green spaces, conservation of water bodies, and sustainable urban design to mitigate the impacts of urban heat in rapidly developing areas like Savar.